(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the results of the conducted pedagogical experiments to study the ability of students to re-adapt to changes in strength and physical qualities and motor activity in physical education classes and to the further development of their health and physical qualities. Currently, in higher educational institutions, there is a systematic reduction in the hours allotted for classes in the discipline “physical education” in the curricula. The specifics of the methodology of classes aimed at developing the physical qualities of students in existing scientific research has not been fully taken into account. Such issues as the proper use of physical education tools, the development of methods of physical education classes for students on circular exercises, its implementation in physical education lessons, as well as the management of the process of improving physical fitness of students, are still relevant. For this reason, we will consider the results of the analysis of this process: shortcomings and achievements.